Impact of soy milk consumption on cardiometabolic risk factors: A systematic review and meta-analysis of randomized controlled trials. (August 2021) - Hassan Sohouli, Mohammad; Lari, Abolfazl; Fatahi, Somaye; Shidfar, Farzad; Găman, Mihnea-Alexandru; Sernizon Guimarães, Nathalia; Sindi, Ghufran Abdullatif; Mandili, Rasha Abdulaziz; Alzahrani, Ghaida Rashed; Abdulwahab, Rahaf Abdulrashid; Almuflihi, Alhanouf Mohammed; Alsobyani, Faris Mohammed; et al.
Graphical abstract: According to the available evidence, soy milk consumption can provide favorable effects on blood pressure, some lipid profile parameters and certain anthropometric and inflammatory markers as compared with a control group. It seems, soy milk consumption is an appropriate strategy to reduce the risk of cardiometabolic diseases. However, further research is recommended to shed light on these findings. Highlights: Soy milk contains essential mono- and poly-unsaturated fatty acids which can exert favorable effects on the cardiovascular health. The current study aimed to comprehensively evaluate the potential effects of soy milk consumption on cardiometabolic risk factors in adults. The quantitative meta -analysis demonstrated that soy milk consumption significantly reduced systolic and diastolic blood pressure, total and low-density lipoprotein cholesterol, waist circumference, C-reactive protein, and tumor necrosis factor-alpha. Abstract: Background: Soy milk contains some beneficial components such as isoflavones which can exert favorable effects on the cardiovascular health. The current study aimed to comprehensively evaluate the potential effects of soy milk consumption on cardiometabolic risk factors in adults. Methods: Relevant articles published up to June 2020 were systematically retrieved from SCOPUS, PubMed/MEDLINE, EMBASE, and Web of Science databases. In our study, we included all the randomized controlled trials (RCTs) investigating the impact of soy milk consumption on various cardiometabolic risk factors in adults (age ≥ 18 years). A meta -analysis of the eligible studies was performed using the random-effects model. Results: The quantitative meta -analysis of 18 eligible RCTs (665 participants, age range 18–65 years) demonstrated that the consumption of soy milk significantly reduced systolic (P < 0.001) and diastolic (P = 0.002) blood pressure, total (P = 0.001) and low-density lipoprotein (P = 0.041) cholesterol, waist circumference (P = 0.005), C-reactive protein (P < 0.001), and tumor necrosis factor-alpha (P = 0.016). Significant between-study heterogeneity was found for the pooled effect sizes of blood pressure and low-density lipoprotein cholesterol. In addition, the subgroup analyses indicated that the decrease in systolic blood pressure (SBP) was more pronounced when soy milk was consumed for ≤ 4 weeks. However, there were no significant differences between soy milk and control groups for the other factors, namely body weight, body mass index (BMI), high-density lipoprotein cholesterol, triglycerides, fasting blood glucose (FBG), and fasting insulin, interleukin-6, and fibrinogen. Conclusions: The current systematic review and meta -analysis revealed that incorporating soy milk into the diet might favorably affect several cardiometabolic risk factors in both healthy and unhealthy individuals.